Efficacy of magnetic resonance imaging with an SPGR sequence for the early evaluation of knee cartilage degeneration and the relationship between cartilage and other tissues - Yang, Xin (J Orthop Surg Res, 2019)
RATIONALE AND OBJECTIVES: The aim of this study was to investigate the efficacy of magnetic resonance imaging (MRI) with a spoiled gradient-recalled (SPGR) sequence to evaluate early knee cartilage degeneration and the relationship between cartilage and other tissues using a modified Whole-Organ Magnetic Resonance Imaging Score (WORMS). MATERIALS AND METHODS: Eighty-four patients with knee joint pain were evaluated by X-ray and MRI with an SPGR sequence from June 2015 to December 2016. Joint degeneration was graded by two experienced radiologists using the Kellgren-Lawrence (K-L) grading scale. The modified WORMS was used to evaluate cartilage lesions, bone marrow abnormalities, bone cysts, osteophytes, joint effusion and synovitis. The difference between the WORMS of the SPGR and the T2 sequences evaluated by the Wilcoxon signed-rank test was determined, and the relationships between the WORMS features were evaluated by a Spearman correlation. RESULTS: The modified WORMS for the cartilage lesion evaluation was significantly higher with the SPGR sequence than with the T2 sequence (P < 0.05). The cartilage lesions showed a moderate correlation with osteophytes, synovitis and joint effusion (Rs > 0.40, P < 0.05) and weak correlations with bone marrow abnormalities and bone cysts (Rs < 0.4, P < 0.05). CONCLUSION: The modified WORMS evaluation using MRI with the SPGR sequence was much better than the normal sequence for early knee osteoarthritis (OA). The cartilage lesions are associated with bone marrow abnormalities and the other features of OA.